Sin garantías: José Aricó, América Latina y la “crisis del marxismo”1 (2019)
The article examined the work of José Aricó, following the hypothesis that Marxism was always in crisis. It analyzed the new beginning of Marxism that Aricó proposed in the context of the Mexican exile, into which he was driven after being expelled from the Communist Party of Argentina and becoming the leading promoter and architect of the neo-left project Pasado y Presente. The paper explored not only the editorial work and the dissemination of ideas that Aricó carried out but also, and especially, the role of critical reader and polemicist who assumes a position within a situation by recognizing his status as a Latin American thinker, without establishing any guarantee.